A real world analysis of NSTE-ACS in more than 4000 patients: accuracy of GRACE and TIMI scores in mortality prediction. (25th November 2020) - Borges-Rosa, J; Ferreira, J; Oliveira-Santos, M; Monteiro, S; Goncalves, F; Monteiro, P; Baptista, R; Goncalves, L
Abstract: Introduction: The TIMI (Thrombolysis in Myocardial Infarction) and GRACE (Global Registry of Acute Coronary Events) risk scores identify high-risk patients with Non-ST elevation acute coronary syndrome (NSTE-ACS) who can benefit from an early invasive strategy. Purpose: We aimed to compare both scores predictive accuracy for mortality in a real-world cohort of patients presenting with NSTE-ACS. Methods: We retrospectively evaluated 4264 patients admitted to our coronary intensive care unit between 2004 and 2017 with a diagnosis of NSTE-ACS. The TIMI and GRACE scores were calculated for each patient, and all-cause mortality was recorded during hospitalization, at one month and one year. To better characterize global troponin release, we defined Total Troponin (TT) as the sum of initial and discharge troponin. We used the area under the receiver operating characteristic curve (AUC) to compare the predictive value of both scores for mortality during hospitalization, at one month and one year. Results: Mean patient age was 67.6±12.4 years and 66.4% were male (n=2833). Mean GRACE score was 124.6±35.8 and mean TIMI score was 2.7±1.6. There was a weak correlation between GRACE and TIMI score (r=0.3, p<0.001). In-hospital mortality was 2.8%: the GRACE score showed higher AUC (0.845, 95% CI 0.805–0.804, p<0.001) compared to TIMI (0.581, 95% CI 0.519–0.643, p=0.009) (Figure 1). Mortality at one month was 5.1%: the GRACE score showed higher AUC (0.842, 95% CI 0.814–0.869, p<0.001) compared to TIMI (0.586, 95% CI 0.541–0.630, p<0.001). Mortality at one year was 11.4%: the GRACE score showed higher AUC (0.811, 95% CI 0.789–0.822, p<0.001) compared to TIMI (0.591, 95% CI 0.560–0.622, p<0.001) (Fig. 1). Analyzing Unstable Angina and Non-ST segment elevation myocardial infarction separately, the GRACE score also showed higher AUC compared to TIMI. Exploratory analyses revealed a combined indicator (GRACE score + TT) which had higher AUC (0.876, 95% CI 0.844–0.907, p<0.001) compared to GRACE score (0.855, 95% CI 0.823–0.887, p<0.001) for one month mortality and for one year mortality (0.818, 95% CI 0.792–0.844, p<0.001 vs. 0.813, 95% CI 0.788–0.839, p<0.001). Conclusion: In patients with NSTE-ACS, GRACE risk score is a better predictor of in-hospital, one month and one-year mortality, compared to TIMI risk score. TT, as a measure of ischemia burden, might improve accuracy of GRACE score in predicting short and long-term mortality. Funding Acknowledgement: Type of funding source: None